Kunsteorie en kunspraktyk: die kunste as ’n hermeneutiek-in-aksie - Olivier, Bert (Koers, 1993)
The present article sets out front Vaclav Havel's observation that there is a strong connection between good taste in art and a sensitivity towards others a n d the environment in the practical domain of life. This assertion is interrogated along the lines of Habermas’s ideal of communicative rationality by exploring the sense in which the 'language’ of art contributes to interpretive communication in the broad sense of the term. Wittgenstein's concept of the plurality of language games is employed in conjunction with the Husserlian idea of the life-world to indicate the role of the arts in presenvig the cognitive and moral-practical richness of this sphere. Two hermeneutic models - those of Schiller a n d Gadamer - are then outlined briefly before concluding with a demonstration of their pertinence for the interjyretation of a filmic artwork, viz. Arcand’s Jesus of Montreal.